Meta Analysis of the Influence of COVID-19 Patient Services on the Level of Anxiety and Depression in Nurses in Hospital - Sudarmono, Andang; Murti, Bhisma; Prasetya, Hanung (Journal of Health Policy and Management, 2022)
Background: The COVID-19 pandemic has spread around the world and is impacting the mental health of everyone, including healthcare workers. Health workers are at the forefront of treating patients infected with COVID-19. are at high risk of experiencing mental health problems during the COVID-19 pandemic. The purpose of this study was to estimate the magnitude of the effect of COVID-19 patient care on the level of anxiety and depression in nurses in hospitals, with a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: nurses. Intervention: serving COVID-19 patients. Comparison: does not serve COVID-19 patients. Outcome: anxiety and depression. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles “Anxiety” AND “Depression” AND “Nurses” OR “Healthcare worker” AND “COVID-19”. The included article is a full-text English language with a cross-sectional study design from 2020 to 2021 and reports the adjusted Odds Ratio (aOR) in a multivariate analysis. The selection of articles is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results:  A total of 12 cross-sectional studies from America, Asia, and Europe were selected for systematic review and meta-analysis. The data collected showed nurses who served COVID-19 patients had a risk of experiencing anxiety as much as 1.75 times compared to nurses who did not serve COVID-19 patients and this result was statistically significant (aOR= 1.75; 95% CI= 1.29 to 2.37; p<0.001 ). A meta-analysis of 12 studies from America, Asia and Europe showed that nurses caring for COVID-19 patients had a 1.1 times risk of developing depression compared to nurses who did not serve COVID-19 patients, but this result was not statistically significant (aOR= 1.10; 95% CI= 0.53 to 2.30; p= 0.80).Conclusion: The effect of caring for COVID-19 patients increases the risk of anxiety and depression in nurses in hospitals.Keywords: Anxiety, Depression, Nurses, COVID-19Correspondence: Andang Sudarmono. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: andan_cf@yahoo.co.id. Mobile: 08156701457.Journal of Health Policy and Management (2022), 07(01): 1-13https://doi.org/10.26911/thejhpm.2022.07.01.01